2017
DOI: 10.1002/kin.21138
|View full text |Cite
|
Sign up to set email alerts
|

Relative Rate Studies of the Reactions of Atomic Chlorine with Acetone and Cyclic Ketones

Abstract: Rate coefficients have been measured for Cl atom reactions under ambient conditions with acetone and four cyclic ketones. Cl was generated by UV photolysis of Cl 2 , and other species were monitored by FT-IR spectroscopy. The measurements yield k(Cl + acetone) = (2.0 ± 0.7) × 10 −12 , k(Cl + cyclobutanone) = (10.1 ± 0.8) × 10 −11 , k(Cl + cycloheptanone) = (24.0 ± 2.3) × 10 −11 , k(Cl + 2-methyl cyclopentanone) = (15.2 ± 1.2) × 10 −11 , and k(Cl + 2-methyl cyclohexanone) = (11.2 ± 1.0) × 10 −11 cm 3 molecule −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Experimental conditions and molecular yields of (E)-4-methylcyclohexanone for the reaction of 4MCHexOH with atmospheric oxidants. Rate coefficient of k= 11.2 × 10 −11 (in cm 3 molecule −1 s −1 ) used to correct the concentration of (E)-4-methylcyclohexanone by loss with the reaction of Cl atoms (data of 2-methylcyclohexanone and Cl atoms Herath et al, 2018). Photolysis rate coefficient estimated for (E)-4-methylcyclohexanone under our experimental conditions, kp = 5 × 10 −5 s −1 .…”
Section: Mchexohmentioning
confidence: 97%
See 2 more Smart Citations
“…Experimental conditions and molecular yields of (E)-4-methylcyclohexanone for the reaction of 4MCHexOH with atmospheric oxidants. Rate coefficient of k= 11.2 × 10 −11 (in cm 3 molecule −1 s −1 ) used to correct the concentration of (E)-4-methylcyclohexanone by loss with the reaction of Cl atoms (data of 2-methylcyclohexanone and Cl atoms Herath et al, 2018). Photolysis rate coefficient estimated for (E)-4-methylcyclohexanone under our experimental conditions, kp = 5 × 10 −5 s −1 .…”
Section: Mchexohmentioning
confidence: 97%
“…This work is the first study of the products of the reaction of 3,3DM1ButOH with atmospheric oxidants; therefore, there is no other study with which to compare the results. Figure 7 shows the reaction mechanism proposed based on existing studies of saturated alcohols' reactions with Cl atoms and the OH radical in the literature (Cavalli et al, 2002;Hurley et al, 2009;McGillen et al, 2013;Welz et al, 2013) and considering the reaction products identified in our work. Table S2 shows a summary of the reaction products, either observed or tentatively identified, proposed in this mechanism of the reaction of 3,3DM1ButOH with the atmospheric oxidants.…”
Section: 3dm1butohmentioning
confidence: 99%
See 1 more Smart Citation